The effect of coal viscosity-temperature characteristics on the dynamic response of slag discharge behavior in Shell gasifier. (1st January 2022) - Lin, Kuo; Shen, Zhongjie; Liang, Qinfeng; Dai, Zhenghua; Xu, Jianliang; Guo, Xiaolei; Liu, Haifeng
Highlights: The plugging behavior of the up-flow gasifier was studied. The effects of slag viscosity characteristics on the slag flow process were studied. The dynamics response of slag flow with operating temperature change was studied. Abstract: How to efficiently and quickly detect the slag blocking behavior of entrained flow gasifiers was an urgent engineering problem. At present, the syngas composition of the gasifier was usually detected to judge whether slag plugging occurred, which had significant hysteresis. In this study, based on the slag dynamic flow model, the influences of operating conditions and slag viscosity-temperature characteristics on the slag discharge behavior of shell gasifiers were investigated. The results showed that the viscosity-temperature characteristics of slag had a great influence on the slag flow response process. The slag steady time and the corresponding steady thickness increased gradually with the transformation of slag type from glassy slag to crystalline slag. When the critical viscosity increased from 9.66 Pa·s to 43.5 Pa·s, the total slag thickness of glassy slag B and crystalline slag D increased by 6.4 and 10.5 cm, respectively. Besides, the slag steady time increased exponentially with the decrease of operating temperature. When the operating temperature dropped by 90 K, the steady-state time of the crystalline slag D reached 210 h.